Atributos fisiológicos de qualidade de sementes de cevada sobre diferentes épocas de colheita e durante o armazenamento - Tunes, Lilian Vanussa Madruga de (2009)
The barley culture (Hordeum vulgare L.) for the beer production it is constituting in one of the more promising and safe agricultural businesses of the country, because it already comes linked to the commercialization process, by previous contract between the producer and the malt industry. In view of this and of the economical answer in relation to other winter cultures, many producers show interest in the inclusion of the barley in their production systems. The objective of this work was to evaluate physiologic attribute of quality about different harvesting periods of barley seeds and during the storage. The seeds used were of the cultivars MN 721 and Scarlett. Harvesting was accomplished when the plants were with 118, 129 and 140 days after the seeding. The seeds were dried in an oven with forced air circulation, until reaching 13% of moisture and then, stored in a cold room and out of the room. After harvesting different methods were tested for overcoming dormancy. The seeds were put for the germination tests, seedling length, mass dry weight, tetrazolium, accelerated aging, seed emergence, electrical conductivity, weight of a thousand seeds, hectolitric weight and also isoenzimatic diferentitation [malato desidrogenase (MDH), alcohol desidrogenase (ADH), acid fosfatase (FAC), glutamate oxalacetato transaminase (GOT) and esterase (EST)]. The results obtained showed that the intensity of dormancy and harvest periods interferes, directly, in the efficiency of the treatments used for overcoming dormancy. Harvesting should be accomplished when the seeds reach the humidity between 26 and 18%. The weight of a thousand seeds influences in a positive way, demonstrating that heavier seeds presented better quality than the light ones. The hectolitric weight, germination and viability tend to decrease as the harvesting period is delayed. There are variations in the pattern of expression of the enzymes EST, ACP, MDH, ADH and GOT between the seeds and seedlings. In the germination process the enzyme EST showed difference between cultivars MN 721 and Scarlett, however it had small variation in the different harvesting periods. In the germination process the enzyme GOT showed variation in the intensity of bands in the different moisture percentages. During storage it was evaluated the physiologic quality of the seeds, at the 3rd and the 6th months, analyzing two atmospheres (cold room and natural conditions). The results were that, the capacity of conservation of barley seeds it is just according to its initial quality.